Mobilizing effort in complex motor tasks: Try-harder instructions in deceptive actions - Böer, Nils Tobias; Steinborn, Michael B.; Weigelt, Matthias; Güldenpenning, Iris (Psychology of Sport and Exercise)
This study investigated whether external effort mobilization through try-harder instructions enhances performance in complex motor tasks, as reflected by the reduction of costs associated with producing a deceptive action. Basketball passing movements with and without head fakes were examined in a reaction-time paradigm. Participants were generally instructed to initiate the movement as fast and accurately as possible, while try-harder instructions were presented in 25 % of trials, prompting participants to mobilize all their cognitive resources to perform even faster. To investigate if athletic expertise modulates the potential effects of effort mobilization, basketball novices and experienced players were tested. Results demonstrated that try-harder instructions generally improved participants’ performance, facilitating faster response initiation times and movement execution, as well as a specific reduction in initiation time variability. Novices benefited more than experienced players, indicating that effort results in greater improvement when complex motor actions (for example, passes with head fakes) are not yet fully stabilized and lack automated fluency. This pattern suggests that effort enhances performance in complex actions when performance is limited by the amount of cognitive capacity available, supporting the coordination of partly conflicting movement components within tight temporal constraints. The findings extend previous research on effort mobilization from simple to complex motor tasks. Try-harder instructions appear to enhance performance primarily by reducing attentional lapses rather than generally improving processing speed. Future research should investigate the effectiveness of effort mobilization in experienced athletes in situations of high concurrent cognitive load.
Keywords: Effort; Try-harder instruction; Deception; Basketball; Head fake; Fake production

Effects of feedback delay duration on neural processing of valence-dependent augmented feedback during motor practice - Margraf, Linda; Krause, Daniel; Maurer, Lisa Katharina; Weigelt, Matthias

Early postural dynamics reveal the rapid processing of fake social cues for deceptive actions in sports - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Schmidt, Thomas; Weigelt, Matthias (18th FEPSAC European Congress of Sport Psychology: Performance, Health and Enhancement in Action)

Mobilizing Effort in Complex Motor Tasks: Try-Harder Instructions in Deceptive Actions - Böer, Nils Tobias; Steinborn, Michael B.; Weigelt, Matthias; Güldenpenning, Iris (18th FEPSAC European Congress of Sport Psychology: Performance, Health and Enhancement in Action)

Early postural dynamics reveal the rapid processing of fake social cues for deceptive actions in sports - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Schmidt, Thomas; Weigelt, Matthias (Scientific Reports)
Abstract Deceptive actions such as head fakes are a hallmark of interactive sports, yet it is not well understood how decisions and whole-body responses to head fakes unfold over time. In the present study, participants viewed video sequences of a basketball player passing to the left or right, either with or without a head fake. In the buzzer task, participants moved laterally to press a response button as if to intercept the pass. In the vocal task, they verbally indicated pass direction. Reaction times (RTs), movement times (MTs), and medio-lateral center-of-pressure (CoP) displacements were recorded to investigate whether motor output is rapid and stimulus-driven or rather requires continuous integration of fake and pass cues. Further, we investigated whether the mere observation of a basketball player leads to overt micromovements even if no response movement is intended. The data analysis shows that head fakes increased RTs in both the buzzer and vocal tasks. In the buzzer task, head fakes induced an initial, small erroneous CoP shift, which was then rapidly corrected. When CoP trajectories were aligned by head orientation, fake and non-fake trajectories diverged shortly after movement onset. In the present dynamic sport-related context, this pattern is more compatible with the early integration of head and pass information than with a strictly sequential prime-target account, although the paradigm differs from classic Rapid Chase Theory designs with discrete primes and target events. In the vocal task, participants were not instructed to move, yet CoP traces showed tiny but systematically lateralized micromovements with a temporal structure resembling that in the buzzer task, albeit without an initial erroneous shift for head fakes. These postural fluctuations are consistent with action-observation-related motor activation, although they do not uniquely identify motor resonance and may also reflect attentional or generalized embodied response tendencies. A clear deceptive response conflict at the postural level emerged only when a lateralized action was prepared.

When Trying Harder Helps: Effort Instructions Affect Performance in Complex Motor Tasks - Böer, Nils Tobias; Steinborn, Michael B.; Weigelt, Matthias; Güldenpenning, Iris (Abstracts of the 68th Conference of Experimental Psychologists)
Keywords: effort; try-harder instruction; deception; sport psychology; action and perception

From interference to priming? Reinterpreting the head-fake effect in basketball through continuous measurements - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (Abstracts of the 68th Conference of Experimental Psychologists)

Strategic adaptations to deceptive actions in sports: The anticipation-response-inhibition-accuracy trade-off - Wickemeyer, Carolin; Weigelt, Matthias; Güldenpenning, Iris (Journal of Sport and Exercise Psychology)

The role of domain-specific expertise on response inhibition in the basketball-specific ARI-task - Wickemeyer, Carolin; Güldenpenning, Iris; Meyer, Johannes; Klatt, Stefanie; Weigelt, Matthias (Abstracts of the 68th Conference of Experimental Psychologists)

Rapid chase or continuous flow of information? Visual-motor processing of head fakes in basketball - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (Abstracts of the 58th Annual Conference of the German Association of Sport Psychology)

The role of domain-specific expertise on response inhibition in the basketball-specific ARI-task - Wickemeyer, Carolin; Güldenpenning, Iris; Meyer, Johannes; Klatt, Stefanie; Weigelt, Matthias (Abstracts of the 58th Annual Conference of the German Association of Sport Psychology)

Unraveling the head-fake effect: Dynamic measures of cognitive conflict in sport contexts - Güldenpenning, Iris; Schulze Freilinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (57. Herbsttagung experimentelle Kognitionspsychologie (HexKop))

How does practice modulate fake-production costs in a basketball task? Analyses of frequency distributions and mixture effects - Böer, Nils Tobias; Schütz, Christoph; Weigelt, Matthias; Güldenpenning, Iris (Psychological Research)
Abstract The execution of incompatible actions imposes costs on action planning, commonly known as response-response incompatibility-costs. This phenomenon is also evident in sports: A basketball player who performs a pass in one direction whilst orienting the head into the contrary direction (pass with head fake) needs more time to initiate the action as if pass direction and head orientation are the same (pass without head fake). The aim of this study was twofold: First, we present a re-analysis of the data from Böer et al. (Psychological Research 88:523–524, 2024) using mixture effect modelling (Miller, Behavior Research Methods 38:92–106, 2006) explore if fake-production costs manifest continuously (uniform effect) in all participants or if some participants show fake-production costs occasionally but substantially (mixed effect). Second, we collected data of a control group which was analysed with the previous data of the practice group and fitted initiation times (ITs) to an ex-Gaussian distribution. The analysis of mixture effects revealed that most participants exhibited a uniform effect when they didn’t have time to mentally prepare the movement. This pattern was not changed by practice, suggesting fake-production costs can’t be overcome by practice alone without mental preparation time. The analysis of mean ITs revealed improvements in the practice group but not in the control group, independent of the type of pass performed. The distribution analyses complemented these findings as it showed that the improvement in participants’ performance with increasing practice can mainly be attributed to a reduction of the exponential part of the distribution (parameter tau).
Keywords: Sport Psychology; Sport Science; Deception; Distribution Analysis

The mere presence of a social partner modulates fake-production costs - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (57th Herbsttreffen der experimentellen Kognitionspsychologie (HExKoP))
Keywords: Deception; Sport Psychology; Social Interaction

Response inhibition for the basketball pump fake with responses of different complexity - Wickemeyer, Carolin; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 56th Autumn Meeting of Experimental Cognitive Psychology (HExKoP))

Effects of the COMT Val158Met polymorphism on neural augmented-feedback processing and motor automatization. - Margraf, Linda; Krause, Daniel; Blischke, Klaus; Arning, Larissa; Weigelt, Matthias

The influence of action outcome probability and expertise on the size of the head-fake effect in basketball - Güldenpenning, Iris; Jackson, Robin C.; Weigelt, Matthias (57. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (ASP))

Differences of producing head fakes with and without a social partner - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (67th Conference of Experimental Psychologists)
Keywords: deception; action preparation; perception; movement planning; sport psychology

Differences of producing head fakes with and without a social partner - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 57th Annual Conference of the German Association of Sport Psychology)

Further information about neural valence-dependent processing of augmented feedback in extensive motor practice: An analysis of frontal theta-band activity - Margraf, Linda; Krause, Daniel; Weigelt, Matthias